Subtract 61/23 and 36/93

61
23
-
36
93
=
2
189
713

What is 61/23 - 36/93

61
23
-
36
93
=

In order to make fractions have the same denominator, multiply the numerator and denominator of each fraction by the denominator of the other

61 x 93
23 x 93
-
36 x 23
93 x 23
=
5673
2139
-
828
2139
=
5673 - 828
2139
=
4845
2139

OR

(61 x 93) - (36 x 23)
23 x 93
=
4845
2139

Simplify the fraction

Divide each part of the fraction with the greatest common factor to simplify the fraction

4845
2139
=
4845 ÷ 3
2139 ÷ 3
=
1615
713

Because the numerator greater than the denominator, so we have an improper fraction, which means we can simplify it by converting the improper fraction to a mixed number.

Improper fraction to mixed number, get the whole number by dividing the numerator with the denominator, then subtract the numerator by the whole number multiplied by the denominator.

1615
713
=
1615 ÷ 713 = 2 +
1615 - (2 x 713)
713
=
2
189
713

Fraction Calculator

📌 Negative signs in fractions

Positive Fractions

-1
-2
=
-
1
-2
=
-
-1
2
=
1
2

Negative Fractions

-1
2
=
1
-2
=
-
-1
-2
=
-
1
2